2011
DOI: 10.1007/s11481-011-9290-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Effects of Opioids—Clinical Relevance

Abstract: Opioid-induced immunosuppression has been demonstrated in cell culture experiments and in animal models. This is in striking contrast to the paucity of confirmatory studies in humans. This review describes the basic pharmacokinetics and -dynamics of opioid use in patients. It summarizes the major findings on opioid use and infectious complications in intensive care unit (ICU) patients, in patients with acute or chronic non-malignant pain, and in intravenous drug users (IDU). The limitations of studies in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 111 publications
0
42
0
2
Order By: Relevance
“…It has also been noticed for a long time that opioids can alter the immune responses. Acute or chronic administration of opioids is known to have inhibitory effects on humoral and cellular immune responses, including antibody production, natural killer-lymphocyte activity, cytokine expression, and phagocytic activity [132][133][134]. Increased morbidity and mortality due to artificial infection and faster cancer progression have been well docu- mented in animal studies with morphine treatment [134,135].…”
Section: Opioid Receptorsmentioning
confidence: 99%
“…It has also been noticed for a long time that opioids can alter the immune responses. Acute or chronic administration of opioids is known to have inhibitory effects on humoral and cellular immune responses, including antibody production, natural killer-lymphocyte activity, cytokine expression, and phagocytic activity [132][133][134]. Increased morbidity and mortality due to artificial infection and faster cancer progression have been well docu- mented in animal studies with morphine treatment [134,135].…”
Section: Opioid Receptorsmentioning
confidence: 99%
“…8 Longer term harms include fractures, falls, endocrine and immune disturbance, disturbance of nocturnal respiratory control, and consequent cardiovascular adverse events. 1116 The prevalence of addiction to prescription opioids is variably reported and may be context-specific. One systematic review suggested that addiction occurs in 8%–12% of individuals taking prescription opioids, but most data in the review derive from the USA and we have no definitive figures for European populations.…”
Section: Opioids and Evidencementioning
confidence: 99%
“…Although opioid-induced immunosuppression has been demonstrated in cell culture experiments and in animal models, there is a paucity of confirmatory studies in humans. The review by Brack et al describes the basic pharmacokinetics and pharmacodynamics of opioid use in patients (Brack et al 2011). It summarizes the major findings of opioid use and infectious complications in intensive care unit patients, in patients with acute or chronic non-malignant pain, and in IDU.…”
Section: Opportunistic Infections Immune Disfunctionmentioning
confidence: 99%